Signal Output of Triboelectric Nanogenerator at Oil–Water–Solid Multiphase Interfaces and its Application for Dual‐Signal Chemical Sensing. Issue 39 (15th August 2019) - Jiang, Peng; Zhang, Lei; Guo, Hengyu; Chen, Chaoyu; Wu, Changsheng; Zhang, Steven; Wang, Zhong Lin
Abstract: A liquid–solid contact triboelectric nanogenerator (TENG) based on poly(tetrafluoroethylene) (PTFE) film, a copper electrode, and a glass substrate for harvesting energy in oil/water multiphases is reported. There are two distinctive signals being generated, one is from the contact electrification and electrostatic induction between the liquid (water/oil) and the PTFE film ( V TENG and I TENG ); and the other is from the electrostatic induction in the copper electrode by the oil/water interfacial charges (Δ V interface and I interface ), which is generated only when the liquid–solid contact TENG is inserted across the oil/water interface. The two signals show interesting opposite changing trends that the V TENG and I TENG decrease while the oil/water interfacial signals of Δ V interface and I interface increase after coating a layer of polydopamine on the surfaces of PTFE and glass via self‐polymerization. As an application of the observed phenomena, both the values of I TENG and I interface have a good linear relationship versus the natural logarithm of the concentration of the dopamine. Based on this, the first self‐powered dual‐signal detection of dopamine using TENG is demonstrated. Abstract : A single‐electrode liquid–solid contact triboelectric nanogenerator (TENG) is fabricated to investigate the signal output at oil–water–solid multiphase interfaces. Two distinctive signals are obtained when the TENG is inserted into the oil/water multiphase. Based on this, the first self‐powered dual‐signal detection of dopamine using a TENG is demonstrated.